KAJIAN HUKUM ISLAM TERHADAP QS. AL-BAQARAH (2): 233 TENTANG BATASAN HUKUM MENYAPIH ANAK DALAM PERSPEKTIF KEWAJIBAN ORANG TUA DAN HAK ANAK - Harahap, Effnida; Syahrul, Syahrul; Zamroni, Surono (Universitas Labuhanbatu, 2025)
This study explores QS. Al-Baqarah (2): 233 within the framework of Islamic law, focusing on the legal boundaries of weaning and its implications for parental duties and children's rights. Using a library research method with a normative-theological and thematic exegesis (maudhu'i) approach, supported by a sociological perspective, this research integrates the concepts of maslahah, justice, and children's rights in Islam. Findings indicate that the verse recommends a two-year breastfeeding period as an ideal, while allowing flexibility based on mutual parental agreement, prioritizing the child's best interest. Keywords: Islamic Law, Legal Limits of Weaning, Parental Obligations, Children's Rights